Utero-placental transfer and fetal utilization of β-hydroxybutyrate in swine - A J Thulin; G L Allee; D L Harmon; D A Schoneweis; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1985)
Utero-placental transfer of Î² hydroxybutyrate (BOHB) in swine was investigated during late gestation using three primiparous sows. There were no measureable artery-vein differences for BOHB concentration in whole blood and concentrations were low in both the sows and fetuses. Radioactive BOHB rapidly crossed the utero-placental unit and was incorporated into the Iiver, adipose, lung, and heart tissue (3540, 3674, 1214, and 528 dpm/g wet weight, respectively). The largest amount of radioactivity for all ti3sues was found in the phospholipid fraction. These data demonstrate that the swine utero-placental unit is permeable to BOHB and indicate that this ketone body is used by the fetus for synthesis of fatty acids and cholosterol for both structural components and energy stores.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; Utero-placental transfer; Î²-hydroxybutyrate; Fetus